Polypeptide Formation by Heating N-t-Butyloxycarbonyl Acidic Amino Acid Derivatives - Munegumi, T.; Meng, Y-Qing; Harada, K. (Asian Journal of Chemistry, 2014)
An acid labile N-protecting group for amino acids, t-butyloxycarbonyl (Boc) group has deprotected at elevated temperatures. The study describes an application of the lability on heating to synthesis of polypeptides from acidic amino acids. t-Butyloxycarbonyl-acidic amino acids (aspartic acid, glutamic acid and b-aminoglutaric acid) and their anhydrides were heated at the higher temperatures than their melting points. Anhydrides of t-butyloxycarbonyl-aspartic acid and t-butyloxycarbonyl-b-aminoglutaric acid gave polypeptides. Thermal analyses of the substrates clarified the pathway of the polypeptide formation.